Lipofilling of the upper eyelid to treat paralytic lagophthalmos. Issue 5 (June 2020) - Biglioli, F.; Rabbiosi, D.; Bolognesi, F.; Cucurullo, M.; Dessy, M.; Ciardiello, C.; Battista, V.M.A.; Tarabbia, F.; Dell'Aversana Orabona, G.; Marchetti, C.; Allevi, F.
Abstract: Lagophthalmos is one of the most unpleasant and dangerous conditions that affect patients with facial palsy. The lack of ocular protection leads to corneal problems (such as conjunctival infections, acute and chronic keratitis, corneal ulcerations, and blindness). A dynamic reanimation of blinking eyelids is the therapeutic gold standard. However, success is not guaranteed with these dynamic techniques; even if results are good, blinking is usually restored within a year of the initial operation. Procedures that act more rapidly and have a higher success rate are needed. We proposed that lipofilling of the upper eyelid would improve eye closure, exploit the advantages of using autologous fat, and avoid the risks of exposure or migration associated with loading the lid with gold. Between 2012 and September 2018, we did upper eyelid lipofilling procedures for 75 patients with unilateral facial palsy. The main favourable result of lipofilling of the upper lid was the immediate improvement in corneal discomfort. Everybody described a partial to total increase in corneal comfort postoperatively. In the treatment of paralytic lagophthalmos, lipofilling of the upper eyelid produces favourable aesthetic and functional results, ocular health is restored, and the patients' quality of life is improved.